Revealing the Hawaiian Believe System about Life, Health, and Creation (Global Journal of Science Frontier Research, 2020)
The author reveals in this article the Hawaiian believe system about life, health, and creation and surprisingly finds that the ancient Hawaiian beliefs agree 100% with her recent scientific measurements and findings about how thoughts influence our body. Positive thoughts increase our energy and make it more balanced, which means positive thoughts make us healthier. Negative thoughts decrease our energy and worsen our balance; they make the energy of the genetically inherited weak organ to drop in energy maximum. This means that each negative thought takes us a step closer to the disease of the genetically inherited weak organ. She found that the ancient Hawaiian beliefs are also in full agreement with the writing in her books, about the creation of the Universe, about intuitive creativity, and about how to find your Soul Mate and have harmonious marriage.
Keywords: hawaiian beliefs; emotions and health; intuitive creativity; finding soul mate; harmonious marriage